Question
upstudy study bank question image url

\( \begin{array}{ll}\text { (a) } \frac{x}{3}-\frac{x}{2}>1 & \text { (b) } \frac{3 x}{4}-x \leq 1 \frac{1}{2} \\ \text { (c) } \frac{y+5}{3}+y \leq 1 & \text { (d) } \frac{3 y+2}{4}-\frac{y-6}{3}>0 \\ \text { (c) }(x+3)(x-4) \leq(x-3)(x+4) & \end{array} \)

Ask by Park Craig. in South Africa
Feb 20,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

Solutions to the inequalities are: - (a) \( x < -6 \) - (b) \( x \geq -6 \) - (c) \( y \leq -\frac{1}{2} \) - (d) \( y > -6 \) - (e) \( x \geq 0 \)

Solution

Solve the inequality by following steps: - step0: Solve for \(x\): \(\frac{3x}{4}-x-\frac{3}{2}\leq 0\) - step1: Multiply both sides: \(\left(\frac{3x}{4}-x-\frac{3}{2}\right)\times 2\times 2\leq 0\times 2\times 2\) - step2: Multiply the terms: \(3x-4x-6\leq 0\) - step3: Simplify: \(-x-6\leq 0\) - step4: Move the constant to the right side: \(-x\leq 0+6\) - step5: Remove 0: \(-x\leq 6\) - step6: Change the signs: \(x\geq -6\) Solve the equation \( \frac{y+5}{3}+y-1<=0 \). Solve the inequality by following steps: - step0: Solve for \(y\): \(\frac{y+5}{3}+y-1\leq 0\) - step1: Multiply both sides: \(\left(\frac{y+5}{3}+y-1\right)\times 3\leq 0\times 3\) - step2: Multiply the terms: \(y+5+3y-3\leq 0\) - step3: Simplify: \(4y+2\leq 0\) - step4: Move the constant to the right side: \(4y\leq 0-2\) - step5: Remove 0: \(4y\leq -2\) - step6: Divide both sides: \(\frac{4y}{4}\leq \frac{-2}{4}\) - step7: Divide the numbers: \(y\leq -\frac{1}{2}\) Solve the equation \( (x+3)(x-4)-(x-3)(x+4)<=0 \). Solve the inequality by following steps: - step0: Solve for \(x\): \(\left(x+3\right)\left(x-4\right)-\left(x-3\right)\left(x+4\right)\leq 0\) - step1: Simplify: \(-2x\leq 0\) - step2: Change the signs: \(2x\geq 0\) - step3: Rewrite the expression: \(x\geq 0\) Solve the equation \( \frac{x}{3}-\frac{x}{2}-1>0 \). Solve the inequality by following steps: - step0: Solve for \(x\): \(\frac{x}{3}-\frac{x}{2}-1>0\) - step1: Multiply both sides: \(\left(\frac{x}{3}-\frac{x}{2}-1\right)\times 3\times 2>0\times 3\times 2\) - step2: Multiply the terms: \(2x-3x-6>0\) - step3: Simplify: \(-x-6>0\) - step4: Move the constant to the right side: \(-x>0+6\) - step5: Remove 0: \(-x>6\) - step6: Change the signs: \(x<-6\) Solve the equation \( \frac{3 y+2}{4}-\frac{y-6}{3}>0 \). Solve the inequality by following steps: - step0: Solve for \(y\): \(\frac{3y+2}{4}-\frac{y-6}{3}>0\) - step1: Multiply both sides: \(\left(\frac{3y+2}{4}-\frac{y-6}{3}\right)\times 4\times 3>0\times 4\times 3\) - step2: Multiply the terms: \(9y+6-4y+24>0\) - step3: Simplify: \(5y+30>0\) - step4: Move the constant to the right side: \(5y>0-30\) - step5: Remove 0: \(5y>-30\) - step6: Divide both sides: \(\frac{5y}{5}>\frac{-30}{5}\) - step7: Divide the numbers: \(y>-6\) Let's solve each inequality step by step: ### (a) \( \frac{x}{3} - \frac{x}{2} > 1 \) 1. **Combine the fractions**: \[ \frac{x}{3} - \frac{x}{2} = \frac{2x - 3x}{6} = \frac{-x}{6} \] So, the inequality becomes: \[ \frac{-x}{6} > 1 \] 2. **Multiply both sides by -6** (remember to reverse the inequality): \[ x < -6 \] ### (b) \( \frac{3x}{4} - x \leq 1 \frac{1}{2} \) 1. **Convert \(1 \frac{1}{2}\) to an improper fraction**: \[ 1 \frac{1}{2} = \frac{3}{2} \] 2. **Rewrite the inequality**: \[ \frac{3x}{4} - x \leq \frac{3}{2} \] 3. **Combine like terms**: \[ \frac{3x}{4} - \frac{4x}{4} \leq \frac{3}{2} \implies \frac{-x}{4} \leq \frac{3}{2} \] 4. **Multiply both sides by -4** (reverse the inequality): \[ x \geq -6 \] ### (c) \( \frac{y+5}{3} + y \leq 1 \) 1. **Combine the terms**: \[ \frac{y+5}{3} + y = \frac{y + 5 + 3y}{3} = \frac{4y + 5}{3} \] 2. **Rewrite the inequality**: \[ \frac{4y + 5}{3} \leq 1 \] 3. **Multiply both sides by 3**: \[ 4y + 5 \leq 3 \] 4. **Isolate \(y\)**: \[ 4y \leq -2 \implies y \leq -\frac{1}{2} \] ### (d) \( \frac{3y+2}{4} - \frac{y-6}{3} > 0 \) 1. **Combine the fractions**: \[ \frac{3y+2}{4} - \frac{y-6}{3} = \frac{(3y+2) \cdot 3 - (y-6) \cdot 4}{12} \] This simplifies to: \[ \frac{9y + 6 - 4y + 24}{12} = \frac{5y + 30}{12} \] 2. **Rewrite the inequality**: \[ \frac{5y + 30}{12} > 0 \] 3. **Multiply both sides by 12**: \[ 5y + 30 > 0 \] 4. **Isolate \(y\)**: \[ 5y > -30 \implies y > -6 \] ### (e) \( (x+3)(x-4) \leq (x-3)(x+4) \) 1. **Expand both sides**: \[ x^2 - x - 12 \leq x^2 + x - 12 \] 2. **Subtract \(x^2 - 12\) from both sides**: \[ -x \leq x \implies -2x \leq 0 \] 3. **Divide by -2** (reverse the inequality): \[ x \geq 0 \] ### Summary of Solutions: - (a) \( x < -6 \) - (b) \( x \geq -6 \) - (c) \( y \leq -\frac{1}{2} \) - (d) \( y > -6 \) - (e) \( x \geq 0 \)

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To solve these inequalities, let's break them down step by step. For (a), \(\frac{x}{3}-\frac{x}{2}>1\): Start by finding a common denominator (which is 6). Rewrite it as \(\frac{2x - 3x}{6} > 1\) leading to \(-\frac{x}{6} > 1\). Multiply through by -6 (and flip the inequality) to get \(x < -6\). For (b), \(\frac{3x}{4}-x \leq 1 \frac{1}{2}\): Rewrite \(1 \frac{1}{2}\) as \(\frac{3}{2}\). This becomes \(\frac{3x - 4x}{4} \leq \frac{3}{2}\) which simplifies to \(-\frac{x}{4} \leq \frac{3}{2}\). Multiplying by -4 (flipping the inequality) gives \(x \geq -6\). Now for (c), \(\frac{y+5}{3}+y \leq 1\): Multiply everything by 3 to eliminate the fraction: \(y + 5 + 3y \leq 3\) simplifies to \(4y + 5 \leq 3\). From here, subtract 5 to result in \(4y \leq -2\), leading to \(y \leq -\frac{1}{2}\). Finally for (d), \(\frac{3y+2}{4}-\frac{y-6}{3}>0\): Clear the denominators by multiplying through by 12, which gives us \(9y + 6 - 4y + 8 > 0\). Combine terms to have \(5y + 14 > 0\), which means \(y > -\frac{14}{5}\). And as a bonus point, for (e), \((x+3)(x-4) \leq (x-3)(x+4)\): Expand both sides to \(x^2 - x - 12 \leq x^2 + x - 12\). Simplifying gives \(-x \leq x\) or \(0 \leq 2x\), leading to \(x \geq 0\). In summary: - For \(x\), it needs to satisfy \(x < -6\) or \(x \geq 0\). - For \(y\), it ranges from \(y \leq -\frac{1}{2}\) and \(y > -\frac{14}{5}\). Inequalities can be puzzling, but remember: always flip that sign when multiplying or dividing by a negative!

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy